On Targets - The Center for Land Use Interpretation CLUI (Footprint)
Impact range targets in military training areas can be square, triangular, rectangular, circular, and linear. Some are designed to look like other things, like airbases, villages, convoys, industrial areas, surface-to-air missile sites, and are built out of old airoplanes, trucks, tanks, cars, buses, boats, tires, mounds of earth, and empty shipping containers. Some are meant to be bombed or strafed physically, others electronically.